Homosexuality as a phenomenon - Shahid , Tehmina; Ismail, Nik Ahmad Hisham (International Journal of Technical Reseach and Application, 2015)
Bismillah al - rahman al - rahim ... In the name of God, the compassionate One, the One who cares. Most religions are very clear on their stance on homosexuality, especially the three monotheistic ones, yet we see an increasing global divide in the opinions regarding the subject, and it seems that most of the condemnation arises from religious beliefs. This paper looks at the psychological and anatomical aspects of sexual orientation and attempts to put forward the idea of revisiting our religious perceptions of homosexuality, to rethink and evaluate our attitudes towards the homosexual individuals of our societies. With the age old debate of whether homosexuality is “born or made”, one thing that can be stated as a fact is that one has little power in choosing their sexual orientation. This alone makes it imperative for the religious advocates to re - visit the idea of homosex uality, as stated in their religion, in order to ensure they are themselves not shunning rightful members of their religious societies. This in no way means challenging God’s Will, but challenging the human perception of The Word of God.